2023
DOI: 10.1002/ps.7374
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and fungicidal activities of novel piperazine thiazole derivatives containing oxime ether or oxime ester moieties

Abstract: BACKGROUND: To study the effect of changing the piperidine ring of oxathiapiprolin on the fungicidal activity, we designed and synthesized novel piperazine thiazole derivatives containing oxime ether or oxime ester moieties, and studied their fungicidal activities against Phytophthora capsici in vitro.RESULTS: These derivatives showed moderate to good fungicidal activities against Phytophthora capsici, two oxime ether derivatives showed higher fungicidal activity in vitro than dimethomorph (EC 50 = 0.1331 ∼g m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Oximes are attractive functional frameworks with widespread applications not only in synthesis but also in medicine and materials chemistry. [4] These compounds have been effectively converted into amides [5] and amines, [6] including nitroalkanes, 1,3-oxazoles, [7] -thiazoles and -diazoles, hydroxylamines, [8] and hydroxylamine O-ethers, nitroalkanes. [9] Typically, oxime anions in solution behave amorphously, but they can function as weak bases (pK b = 12) and weak acids (pK a = 11).…”
Section: Synthesis Of Aldoxime and Ketoximesmentioning
confidence: 99%
“…Oximes are attractive functional frameworks with widespread applications not only in synthesis but also in medicine and materials chemistry. [4] These compounds have been effectively converted into amides [5] and amines, [6] including nitroalkanes, 1,3-oxazoles, [7] -thiazoles and -diazoles, hydroxylamines, [8] and hydroxylamine O-ethers, nitroalkanes. [9] Typically, oxime anions in solution behave amorphously, but they can function as weak bases (pK b = 12) and weak acids (pK a = 11).…”
Section: Synthesis Of Aldoxime and Ketoximesmentioning
confidence: 99%
“…23 Fungicidal Mechanism Research. Scanning electron microscopy (SEM) observations on the hyphae of Physalospora piricola were conducted according to the reported method; 24 the detailed methods can be seen in the Supporting Information.…”
Section: Preparation Of Compound 5-bromo-2-methyl-3-(p-tolyl)cyclopen...mentioning
confidence: 99%
“…[23][24] Flavonols and quinazolinones have a wide range of biological activities, the active splicing method has been widely used in the development of new pesticides. [25][26][27] Therefore, 20 flavonol derivatives containing quinazolinone were designed, synthesized and evaluated for their antiviral activity by using the natural product flavonol as a lead compound and introducing quinazolinone moiety (Figure 1). Bioassays demonstrated that K5 exhibited the better antiviral activity compared with that of NNM.…”
Section: Introductionmentioning
confidence: 99%